From consumers to investors: an investigation into the character and nature of stokvels in South Africa's urban, peri-urban and rural centres using a phenomenological approach - Mulaudzi, Rudzani (Research of GSB, 2017)
Stokvels are South Africa's version of Rotating Savings and Credit Associations (ROSCAs) or Accumulating Savings and Credit Associations (ACSAs). There are over 820 000 stokvels with a combined membership of 11.4 million people and handling over R44 billion per annum. It is well documented that the majority of the funds that stokvels handle are spent on consumables. This research sought to determine how to transition these stokvels from pure consumers to investors. In order to answer the research question, phenomenology was used as a research method. Focus groups and semi-structured interviews were used as the research instrument. After spending six months with 36 stokvels, the research findings show that there are six factors that influence the current consumption patterns of stokvels. These also provide key insight on how stokvels can be transitioned from consumers to investors. Of the six factors, two of them were identified as key inhibitors to this transition. One being financial institutions, specifically banks, which have built their entire product offering to stokvels based on a small aspect of their governance (constitution and key roles). Second is members' reliance on the stokvels funds for livelihoods. This makes them risk averse as they cannot afford to lose their money nor delay their expenditure. The research also shows that financial education is central to the transition from consumers to investors, specifically seeing, reading or hearing of the financial successes of other stokvels.